2015
DOI: 10.1016/j.neuroimage.2015.05.029
|View full text |Cite
|
Sign up to set email alerts
|

4D MEMRI atlas of neonatal FVB/N mouse brain development

Abstract: The widespread use of the mouse as a model system to study brain development has created the need for noninvasive neuroimaging methods that can be applied to early postnatal mice. The goal of this study was to optimize in vivo three-(3D) and four-dimensional (4D) manganese (Mn)-enhanced MRI (MEMRI) approaches for acquiring and analyzing data from the developing mouse brain. The combination of custom, stage-dependent holders and self-gated (motion-correcting) 3D MRI sequences enabled acquisition of high-resolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
94
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 62 publications
(95 citation statements)
references
References 62 publications
(87 reference statements)
1
94
0
Order By: Relevance
“…This development of an embryonic 4D atlas shares several ideas with a study by Szulc et al, which used in vivo 3D magnetic resonance imaging and image registration to describe the anatomical development of postnatal mouse brain (Szulc et al, 2015).…”
Section: Development Of a Novel Staging Systemmentioning
confidence: 71%
“…This development of an embryonic 4D atlas shares several ideas with a study by Szulc et al, which used in vivo 3D magnetic resonance imaging and image registration to describe the anatomical development of postnatal mouse brain (Szulc et al, 2015).…”
Section: Development Of a Novel Staging Systemmentioning
confidence: 71%
“…2), when the majority of granule cells are generated (Sudarov & Joyner, 2007; Legué et al , 2015; Szulc et al , 2015). Histological analysis clearly revealed the increase in cerebellum size and complexity of foliation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Conversion between cell numbers and tissue areas was made using the following simple formula: Nnormalo,normali=Anormalo,normali×Lvc where v c is the volume of a granule cell, assumed to be 300-μm 3 (Mares et al, 1970; Seil & Herndon, 1970; Altman & Bayer, 1997), and L is the medial-lateral width (measured in μm) of the vermis (central cerebellum), containing lobule III from which we measured the data. Both histological and MRI studies have shown that L is relatively constant over the early postnatal developmental period, with most of the growth of the cerebellum occurring in the anterior-posterior direction, along the length of each of the lobules (Legué et al , 2015, Szulc et al , 2015). From MRI data (Szulc et al , 2015), we estimated L (measured along the medial-lateral outer contour of the vermis) to be 1775-μm (± 20%) between P2 and P14.…”
Section: Mathematical Modelmentioning
confidence: 99%
See 2 more Smart Citations